Measuring Intimate Partner Violence and Traumatic Affect: Development of VITA, an Italian Scale - Gina Troisi (Frontiers in Psychology, 2018)
In a global context where the percentage of women who are victim of violence is still high (World Health Organization, 2013), intimate partner violence (IPV) can be considered the most widespread form of violence against women: in such cases violent attacks are perpetuated or threatened by a partner or ex-partner within an intimate relationship, which makes its recognition more difficult. IPV requires specific tools and, although the literature has highlighted the specific role played by some emotions (such as shame, guilt, and fear) that keep women experiencing this violence in a state of passivity and confusion, to date too little attention has been given to the construction of sound instruments able to detect post-traumatic affectivity. Such instruments could facilitate women who have suffered from IPV in recognizing it and in making the responses of women’s health services more sensitive and structured. This study illustrates a sequential item development process to elaborate a new self-report instrument (VITA Scale: Intimate Violence and Traumatic Affects Scale) for assessing the intensity of post-traumatic affect derived from IPV. Within a psychodynamic perspective, the scale is characterized by four affects: fear, as a state of alarm elicited by the avoidance of the danger; terror, as a paralyzing state that hinders an active process of reaction; shame as a strong exposure to the other that disarms the individual and the guilt as a defensive dimension aiming at the restoring of the link with the abusive partner. Trough specific methodological steps, a 28-item set was selected and administered to a sample of 302 Italian women who declared themselves as having suffered from IPV. Explorative and confirmatory factor analysis, as well as correlations with well-established concurrent tools were computed in order to investigate its psychometric property. A factorial structure composed of four factors, consistent with theoretical scales and a good internal consistency (Cronbach’s alphas from 0.80 to 0.90) emerged. The VITA Scale could be a useful tool for clinicians and researchers to investigate the intensity of the affective state of the woman suffered from IPV. It could be useful to better address the clinical practice and therapeutic intervention planning.